Synthesis and characterization of Gd2O3 doped UO2 nanoparticles - Soldati, Analía Leticia (2016)
UO2 nanoparticles doped with 4, 8, 10 and 15 wt% Gd2O3were synthesized by a reverse strike method. Crystal structure and chemical homogeneity were evaluated using a combination of X-ray diffraction and microscopy tools. An exhaustive study of the composition and its homogeneity at the micro and at the nanometer level was carried out in this nuclear fuel material. Field Emission Gun Scanning and Transmission Electron Microscopy images revealed the presence of micrometer scale agglomerates of nanoparticles, with rounded morphology and an average crystallite size of 100 nm. Rietveld refinements of high-statistic X-ray Diffraction data determined the crystal structure and composition. Furthermore, Energy Dispersive Spectroscopy using a 2 nm2 spot on the sample surface determined a Gd concentration variation around the average of ±5% in different spots of a single crystallite and of ±10% between different crystallites. However, when measuring large amounts of nanoparticles the concentration averages, producing a homogeneous composition distribution at the micrometer scale.